Tech on the ROC: Export threshold and technology adoption interacted - Stefano Costa; Federico Sallusti; Claudio Vicarelli; Davide Zurlo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This paper analyses the potential mismatch between the conditions required for a manufacturing firm to become exporter and the pattern of technology adoption within the industry. The "export threshold", which is estimated using the ROC methodology, is the minimum combination of productivity and "economic size" (a broader measure of firm size) that firms need to achieve in order to access export markets. To consider the pattern of technology adoption we also estimate a "technology line". The relative positioning of the "technology line" and the export threshold generates a new taxonomy of firms allowing for better policies for internationalization.
Keywords: F14; L60; L11; O14; 330; ROC analysis; export threshold; technology adoption; extensive margin of exports